Development of Edu-Kit Media for Entrepreneurship Learning based on Gamification Model Toward Disruptive Education - Kusdiyanti, Heny; Karkono; Sopingi; Febrianto, Indra; Wijaya, Robby; Agustina, Nur Indah (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The current fact shows that entrepreneurship education is only a textbook without providing experimental learning to students. The current solutions have not been able to accommodate the needs of students, especially in the era of disruptive education which is developing massively. This study aims to develop gamification-based educational learning media that will be implemented in high school students to develop students' entrepreneurial spirit. This type of research is development research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method by using a questionnaire to collect research data. After being implemented, gamification-based educational learning media succeeded in increasing student interest in entrepreneurship education as a provision for the growth of the entrepreneurial spirit in students. This learning media has also succeeded in increasing the activeness of teachers and students in the learning process that provides experimental learning to students. The collaboration between the gamification model and educational learning media is by the competency needs of students in the current era of disruptive education. Follow-up research is deemed necessary that focuses on digitizing gamification-based educational media that was developed without eliminating the activeness of teachers and students in learning